Numerical Simulation of Combustion and Rotor-Stator Interaction in a Turbine Combustor - Dragos D. Isvoranu; Paul G. A. Cizmas (International Journal of Rotating Machinery)
This article presents the development of a numerical algorithm for the computation of flow and combustion in a turbine combustor. The flow and combustion are modeled by the Reynolds-averaged Navier-Stokes equations coupled with the species-conservation equations. The chemistry model used herein is a two-step, global, finite-rate combustion model for methane and combustion gases. The governing equations are written in the strong conservation form and solved using a fully implicit, finite-difference approximation. The gas dynamics and chemistry equations are fully decoupled. A correction technique has been developed to enforce the conservation of mass fractions. The numerical algorithm developed herein has been used to investigate the flow and combustion in a one-stage turbine combustor.